Employee Service Performance towards Priority Customer Loyalty at PT. Bank Sumut Syari'ah Medan Branch Katamso - Muhammad Rizky; Sugianto Sugianto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Service is often an assessment in the banking sector, even not only in the banking sector, in various other sectors this service is a concern and assessment for every customer or consumer who uses the product. This service is one of the factors that greatly influences the development of a company because of the effect of the service itself, namely customer or customer satisfaction. Therefore, this research was conducted using interview techniques and direct observation on employees and priority customers of Bank PT. Bank Sumut Syari'ah Medan Katamso Branch. It aims to determine the service of employees to their priority customers. The results of the study indicate that by providing good service in the form of a fast response, good communication, features and facilities that are qualified will make customers feel confident, trust and feel comfortable to continue to be a priority customer at the bank they choose.